Prevalence of premenstrual syndrome and quality of life among health science college student - Dwi Kustriyanti; Hermeksi Rahayu (Intelektual Pustaka Media Utama, 2020)
Premenstrual syndrome (PMS) is a set of affective, behavioral and physical symptoms with appear in the luteal phase that could affect productivity and quality of life. PMS in adolescents could affect academic performance, such as a decreasing in concentration, failed the exam and absenteeism in the class. The objective was to evaluate the prevalence of PMS and determine its effect on quality of life among female health science students. This cross-sectional study was conducted between July-September 2017 on nursing female students of Health Science Collage “Karya Husada Semarang”, Central a Java, Indonesia. Students were enrolled 207 from first to fourth grade using WHOQOL–BREF form to determine quality of life. Inclusion criteria were having regular menstrual cycles (21-35 days) at least three period. Descriptive analysis and Mann Whitney tests were used for statistical analyses. The prevalence of PMS was found to be 60.8%. Physical health, psychological, social relationship, and environment domain were significantly higher in females with PMS (for each one P < 0.05).